2020
DOI: 10.1155/2020/8685126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Six Cases of Tracheobronchopathia Osteochondroplastica

Abstract: Objective. To investigate the clinical characteristics of tracheobronchopathia osteochondroplastica (TO). Methods. The clinical data of six patients with TO from November 2016 to November 2018 were retrospectively analyzed. The etiology, clinical manifestations, diagnosis, and treatment of TO were summarized. Result. All six patients with TO were middle-aged males, confirmed by histopathological examination. The main clinical symptoms were cough, sputum, hemoptysis, chest pain, and repeated pulmonary infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
1
6
0
4
Order By: Relevance
“…Some reports have found that the most frequent presentation is chronic cough and dyspnea, 9 which were complaints voiced by our subjects. Some patients also have restrictive or pulmonary ventilation dysfunction 10 ; our patients had slightly anormal pulmonary function.…”
Section: Discussionmentioning
confidence: 57%
“…Some reports have found that the most frequent presentation is chronic cough and dyspnea, 9 which were complaints voiced by our subjects. Some patients also have restrictive or pulmonary ventilation dysfunction 10 ; our patients had slightly anormal pulmonary function.…”
Section: Discussionmentioning
confidence: 57%
“… 3 Although TO is rare, there have been many reports in which it was occasionally diagnosed. 1 , 4 27 To date, only a limited number of studies have utilized extensive data to conduct a comprehensive investigation of this disease. 3 , 28 …”
Section: Introductionmentioning
confidence: 99%
“…La traqueobroncopatía osteocondroplástica es una rara enfermedad, crónica benigna, caracterizada por múltiples nódulos cartilaginosos u óseos submucosos, que se proyectan en la luz de los dos tercios inferiores de la tráquea y la parte superior de los bronquios principales [1]. En algunos casos, la laringe y la tráquea subglótica también pueden estar comprometidas [2,3], causando diversos síntomas respiratorios.…”
Section: Introductionunclassified